The Influence Of Work-Family Conflict To Organizational Commitment Mediated By Job Satisfaction (Study On Female Lecturer In Muhammadiyah University Of Yogyakarta) - Apriani, Rizki; Qamari, Ika Nurul (Universitas Muhammadiyah Yogyakarta, 2016)
The purpose of this research is to identify the influence of Work Interfering Family and Family Interfering Work toward the Organizational Commitment that mediated by Job Satisfaction. Information of this research is useful for organization (Univesity) as a consideration base to improve work achievement. The subject in this reseach is female lecturer in Muhammadiyah University of Yogyakarta. Purposive sampling is the method that used in this research. The method to collect the data is by spreading the questionnaire, and through this method, researcher gained 110 lecturer as respondent. The data is analyzed by Structural Equation Modeling (SEM).The result of this research shows that the of Work Interfering Family has a significant negative effect on Job Satisfaction, and Family Interfering Work has a negative effect yet insignificant toward Job Satisfaction, and Job Satisfaction has a positive effect and significant on Organizational Commitment. This research is also shows that of Work Interfering Family has a positive effect and significant towards Organizational Commitment, and Family Interfering Work has a positive effect and insignificant toward Organizational Commitment